An Evidence Based Analysis of Employee Satisfaction: The Effect of Leadership, Work Environment and Motivation - Tri Suyantiningsih , Siswoyo Haryono; M. Holil (International Journal of Advanced Science and Technology, 2020)
This research aimed to examine the effect of leadership and work environment on motivation and its impact on employee job satisfaction. The sample of this research is 100 people from 403 employees of Malang Centerpoint Department Store, Malang City, East Java, Indonesia. The analysis employed the Structural Equation Model (SEM) with the Smart PLS 3.2 program. Measurement of variables using questionnaires with a test of validity and reliability. The results showed: (1) Leadership significantly affects work motivation. (2) The work environment does not affect work motivation. (3) Leadership does not affect job satisfaction. (4) The work environment significantly affects the employee job satisfaction. (5) Work motivation significantly affects employee job satisfaction. From the results of mediation analysis and total effect, employees’ work motivation significantly mediated the effect of leadership on job satisfaction. Employees’ work motivation also significantly mediated the effect of the work environment on job satisfaction. While the most significant total effect is 0.362, located in the pathway of the work environment, motivation, and job satisfaction. The managerial implications for increasing job satisfaction are the most effective by increasing variables on the path to the work environment, work motivation, and job satisfaction